Single Dose of Bivalent H5 and H7 Influenza Virus-Like Particle Protects Chickens Against Highly Pathogenic H5N1 and H7N9 Avian Influenza Viruses - Hu, Jiao; Peng, Peipei; Li, Jun; Zhang, Qi; Li, Rumeng; Wang, Xiaoquan; Gu, Min; Hu, Zenglei; Hu, Shunlin; Liu, Xiaowen; Jiao, Xinan; Peng, Daxin; et al. (Frontiers in Veterinary Science, 2021)
Both H5N1 and H7N9 subtype avian influenza viruses cause enormous economic losses and pose considerable threats to public health. Bivalent vaccines against both two subtypes are more effective in control of H5N1 and H7N9 viruses in poultry and novel egg-independent vaccines are needed. Herein, H5 and H7 virus-like particles (VLPs) were generated in baculovirus expression system and a bivalent H5+H7 VLP vaccine candidate was prepared by combining these two antigens. Single immunization of the bivalent VLP or commercial inactivated vaccines elicited effective antibody immune responses, including hemagglutination inhibition, virus neutralizing and HA-specific IgG antibodies. All vaccinated birds survived lethal challenge with highly pathogenic H5N1 and H7N9 viruses. Furthermore, the bivalent VLP significantly reduced viral shedding and virus replication in chickens, which was comparable to that observed for the commercial inactivated vaccine. However, the bivalent VLP was superior to the commercial vaccine in terms of alleviating pulmonary lesions caused by H7N9 virus infection in chickens. Therefore, our study suggests that the bivalent H5+H7 VLP vaccine candidate can serve as a critical alternative for the traditional egg-based inactivated vaccines against H5N1 and H7N9 avian influenza virus infection in poultry.